2014
DOI: 10.1177/0310057x1404200413
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Acute Liver Failure and Extreme Hypoglycaemia with Lactic Acidosis who was not in Coma: Causes and Consequences of Lactate-Protected Hypoglycaemia

Abstract: Lactate can substitute for glucose as a metabolic substrate. We report a patient with acute liver failure who was awake despite a glucose level of 0.7 mmol/l with very high lactate level of 25 mmol/l. The hypoglycaemia+hyperlactataemia combination may be considered paradoxical since glucose is the main precursor of lactate and lactate is reconverted into glucose by the Cori cycle. Literature relevant to the underlying mechanism of combined deep hypoglycaemia and severe hyperlactataemia was assessed. We also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This association was independent of BG concentrations, although BG concentrations were also significantly associated with l ‐lactate concentrations. As the close correlation between the 2 parameters highlights, BG and L‐lactate concentrations are interconnected metabolites in the carbohydrate metabolism and each can lead to the generation of the other . Anaerobic glycolysis of glucose generates l ‐lactate as an end product while l ‐lactate, via generation of pyruvate, can initiate gluconeogenesis or glycogen formation .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This association was independent of BG concentrations, although BG concentrations were also significantly associated with l ‐lactate concentrations. As the close correlation between the 2 parameters highlights, BG and L‐lactate concentrations are interconnected metabolites in the carbohydrate metabolism and each can lead to the generation of the other . Anaerobic glycolysis of glucose generates l ‐lactate as an end product while l ‐lactate, via generation of pyruvate, can initiate gluconeogenesis or glycogen formation .…”
Section: Discussionmentioning
confidence: 97%
“…As the close correlation between the 2 parameters highlights, BG and L-lactate concentrations are interconnected metabolites in the carbohydrate metabolism and each can lead to the generation of the other. 11,12 Anaerobic glycolysis of glucose generates L-lactate as an end product while L-lactate, via generation of pyruvate, can initiate gluconeogenesis or glycogen formation. 13 In septic human patients, 45% of L-lactate is converted into glucose either by gluconeogenesis or glycogen production.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate levels have been shown to be significantly higher in patients with early hepatic dysfunction in the setting of acute circulatory failure [ 31 ] and the a priori presence of liver dysfunction as defined by previous medical history or initial laboratory measurements at presentation is significantly associated with impaired lactate normalization during resuscitation of severe sepsis and septic shock [ 32 ]. During acute liver failure, such as after paracetamol intoxication, gluconeogenesis can be extremely impaired with very elevated lactate levels (>20 mmol/L) and deep hypoglycemia (<1 mmol/L) [ 33 ]. Our study showed that patients with discrepantly elevated lactate and decreased glucose subsequently developed higher bilirubin levels and liver enzymes (Additional file 2 : Figures S11 and S12) compared to patients with elevations of both lactate and glucose.…”
Section: Discussionmentioning
confidence: 99%
“…When coupled with results from our previous study (Hartman et al, 2010;Rodrigues et al, 2011), this new concept concerning the role of lactate as a brain fuel (Pellerin, Magistretti, 2012;Proia et al, 2016;Smith et al, 2003), suggests the possibility of using lactate rather than glucose to treat insulin induced hypoglycemia (Chan et al, 2013;De Feyter et al, 2013;Herzog et al, 2013;Oldenbeuving et al, 2014;Rooijackers et al, 2016).…”
Section: Introductionmentioning
confidence: 59%